2016
DOI: 10.1016/j.envres.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Estimating daily air temperature across the Southeastern United States using high-resolution satellite data: A statistical modeling study

Abstract: Accurate estimates of spatio-temporal resolved near-surface air temperature (Ta) are crucial for environmental epidemiological studies. However, values of Ta are conventionally obtained from weather stations, which have limited spatial coverage. Satellite surface temperature (Ts) measurements offer the possibility of local exposure estimates across large domains. The Southeastern United States has different climatic conditions, more small water bodies and wetlands, and greater humidity in contrast to other reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 29 publications
1
37
1
Order By: Relevance
“…A direct comparison of the performance of the Antarctica T air product to other studies is difficult, not only due to differing environments and temporal scales, but most particularly due to different validation methods being used. Benali et al, Hengl et al and Shi et al [15,43,44] found considerably higher agreement between measured and predicted T air by including auxiliary variables in their models (RMSE usually below 2.5 • C). However, their model training and validation strategies do not rely on LOSOCV.…”
Section: Discussionmentioning
confidence: 99%
“…A direct comparison of the performance of the Antarctica T air product to other studies is difficult, not only due to differing environments and temporal scales, but most particularly due to different validation methods being used. Benali et al, Hengl et al and Shi et al [15,43,44] found considerably higher agreement between measured and predicted T air by including auxiliary variables in their models (RMSE usually below 2.5 • C). However, their model training and validation strategies do not rely on LOSOCV.…”
Section: Discussionmentioning
confidence: 99%
“…So far, LM is one of the most popular statistical models for T a estimation using MODIS LST [14,17,22,25,36,37]. Although it was found that the correlation between LST and T a is high, this relationship may not actually be linear [18].…”
Section: Algorithms Usedmentioning
confidence: 99%
“…Several studies have shown that the vegetation cover on the surface can affect LST values [53]. Vegetation cover (NDVI) data are provided every 16 days at 1-kilometer spatial resolution from the MODIS satellite, including MOD13A2 (TERRA 16-days period starting Day 001) and MYD13A2 (AQUA 16-day period starting Day 009).…”
Section: Vegetation Based On Ndvimentioning
confidence: 99%